EFFECT OF TETRABIOTIC PROBIOTIC ON QUANTITATIVE AND QUALITATIVE INDICATORS OF BROILER CHICKEN MEAT (Neo Science Peer Reviewed Journal, 2024)
In these studies, for the first time in the conditions of Uzbekistan, the effect of TETRABIOTIC probiotic ROSS-308 on the meat productivity, growth and development of broiler chickens was studied. Meat yield, growth and development, metabolism, blood biochemical indicators, productivity, broiler chicken meat quality indicators were evaluated when TETRABIOTIC probiotic was used in the care of chickens. Effect of TETRABIOTIC probiotic on the quality of meat products in the diet of probiotic ROSS 308 broiler chickens was determined.